SYNTHESIS OF FINE DISPERSIVE HIERARCHICALLY STRUCTURED FILLERS FOR THE CREATION OF TEXTURED SUPERHYDROPHOBIC SURFACES - Valtsifer, V.A.; Lebedeva, I.I.; Starostin, A.S. (Perm Federal Research Centre Journal, 2017)
The methods have been proposed for synthesis of inorganic fillers with a hierarchical structure based on finely divided aluminum oxide to produce textured superhydrophobic surfaces. We have studied the effect of the prescription and process parameters on the morphology, texture properties, dispersibility and particle size distribution, as well as modality of the hierarchical structure. The mechanism of formation of hierarchical structures and the ways of its modification have also been examined. A technique for alumina spherulite water-repellency treatment has been proposed, the complex of physical and chemical research, aimed at studying the hydrophobic properties of the obtained fillers, the optimization of quantitative and fractional composition of the fine hydrophobized fillers in the polymer matrix has been carried out. The approaches to the production of composite materials to create textured superhydrophobic surfaces were couched.